NILAI-NILAI PENDIDIKAN ISLAM MULTIKULTURAL PADA BUDAYA RITUAL MANDI SUCI AIR KEHIDUPAN CANDI BELAHAN DI KABUPATEN PASURUAN - Pulung Mohamad Supriyadi; Achmad Yusuf (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2022)
Culture is an activity that is built on creativity, a sense of initiative. Culture is able to survive because it is accepted by society and is useful. The island of Java which originally had the Kapitayan culture known as supernatural powers. Wonosunyo Village, Gempol District, Pasuruan Regency has a culture. This culture is called the ritual culture of the sacred bathing water of Candi Belahan. The ritual culture of bathing in the holy water of life at Candi Belahan is an activity carried out with various purposes and objectives. Some are aimed at treating medical or non-medical illnesses, some are aimed at increasing knowledge of kanuragan, some are aimed at maintaining the condition of the body to stay young and some are aimed at gratitude for the blessings that have been received and all these goals are addressed to Allah SWT as the ruler. natural. The culture must have undergone a process of cultural assimilation. This happened because in the past the Candi Belahan area was an area where the Kapitayan culture was able to shift to an Islamic culture that unites Allah SWT. The focus of this research includes: what are the values of multikultural Islamic education in the ritual culture of the sacred bathing water of Belahan Temple. The method in this study uses a phenomenological approach. The data of this study consisted of primary data and secondary data. Data were collected by interview, observation and documentation techniques. Data analysis techniques include 1) making a list, 2) initial grouping of data, 3) reduction and, 4) data elimination. The results of this study found: The values of multikultural Islamic education in the ritual culture of the sacred bathing water of Candi Belahan are the values of aqidah (religion), shari'ah (mutual respect, human rights and obligations), morals (al-akhlak al- fardiyah, al-akhlak al-ijtimaiyah, and al-akhlak al-diniyah).